2016
DOI: 10.1094/mpmi-03-15-0047-r
|View full text |Cite
|
Sign up to set email alerts
|

OsGF14b Positively Regulates Panicle Blast Resistance but Negatively Regulates Leaf Blast Resistance in Rice

Abstract: Although 14-3-3 proteins have been reported to be involved in responses to biotic stresses in plants, their functions in rice blast, the most destructive disease in rice, are largely unknown. Only GF14e has been confirmed to negatively regulate leaf blast. We report that GF14b is highly expressed in seedlings and panicles during blast infection. Rice plants overexpressing GF14b show enhanced resistance to panicle blast but are susceptible to leaf blast. In contrast, GF14b-silenced plants show increased suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 54 publications
4
67
0
Order By: Relevance
“…In addition, Os GF14e can interact with DOF ZFP transcription factors that were activated by developmental signals in plants (Cooper et al, 2003). Interestingly, the silencing of OsGF14e displayed impaired seed development in rice which resembles our current observation (Manosalva et al, 2011; Liu et al, 2016). Moreover, earlier evidences suggested that the higher accumulation of GF14e protein was associated with fertile pollen grains of maize while lesser abundance of the protein was found in sterile pollens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, Os GF14e can interact with DOF ZFP transcription factors that were activated by developmental signals in plants (Cooper et al, 2003). Interestingly, the silencing of OsGF14e displayed impaired seed development in rice which resembles our current observation (Manosalva et al, 2011; Liu et al, 2016). Moreover, earlier evidences suggested that the higher accumulation of GF14e protein was associated with fertile pollen grains of maize while lesser abundance of the protein was found in sterile pollens.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, two GF14 family members, Os GF14b and Os GF14e were demonstrated to positively regulate leaf blast resistance in plants (Manosalva et al, 2011). Also, the suppression of Os GF14e and Os GF14b could produce susceptibility towards panicle blast (Manosalva et al, 2011; Liu et al, 2015, 2016). In addition, Os GF14e can interact with DOF ZFP transcription factors that were activated by developmental signals in plants (Cooper et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster D7 consists of 2 genes (OsGF14b and OsGF14e) that belong to 14-3-3 gene family. These signaling proteins are reported to be involved in biotic stress and probably associated with JA and SA pathways [150,151]. They interact with Beta-2-and Beta-5-tubulin proteins which play critical role in cell division, elongation and growth.…”
Section: Resultsmentioning
confidence: 99%
“…Although a positive correlation was observed between leaf blast resistance and neck blast resistance, this is not always the case (Zhuang et al 2002). Liu et al (2016) evaluated 31 near-isogenic lines' resistance to rice blast, and they found that several lines exhibited resistance to leaf blast but were not resistant to neck blast, and vice versa. Liu et al (2016) also studied differential regulation functions of 14-3-3 proteinon, which is associated with biotic stress in plants on leaf blast and neck blast.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2016) evaluated 31 near-isogenic lines' resistance to rice blast, and they found that several lines exhibited resistance to leaf blast but were not resistant to neck blast, and vice versa. Liu et al (2016) also studied differential regulation functions of 14-3-3 proteinon, which is associated with biotic stress in plants on leaf blast and neck blast. They concluded that leaf blast and neck blast resistance was controlled by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%